ASSESSMENT OF TREE SPECIES USED AS SHELTERBELT IN THE SEMI-ARID PART OF YOBE STATE, NIGERIA - B. L. Gadiga (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2018)
This study examines the type of tree species used in the establishment of shelterbelts in the semi-arid parts of Yobe State, northeastern Nigeria. The study uses both primary and secondary sources of data in order to ascertain the success of the species used in shelterbelts establishment in the zones. The study shows that Azadirachta indica is the most frequently used species and the most successful in the area. Others with relative importance are Acacia spp and Eucalyptus camaldulensis. Their success and preference are because of their xerophytic characteristics which enable them to survive long dry seasons. It also reveals that the farmers prefer indigenous economic trees like Acacia nilotica, Hyphaene thebaica and Balanites aegyptiaca because of economic and social benefits derived from the trees. Therefore the study recommends that Government should encourage the involvement of local people in the planning and management of shelterbelt programmes and generally afforestation projects in arid zones.